2007
DOI: 10.5507/bp.2007.051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on the Onset and Duration of Rocuronium-Induced Neuromuscular Block

Abstract: Aims:To assess the infl uence of gender on the course of rocuronium-induced neuromuscular block following a single bolus dose of 2 × ED 95 (0.6 mg kg -1 ). Methods: Following the ethics committee approval and informed consent, 245 patients (121 men, 124 women) scheduled for elective general surgery under TIVA with muscle relaxation were studied. After rocuronium 0.6 mg kg -1 , the onset time for maximal depression of T 1 , clinical duration until 25 % recovery and recovery index (T 1 from 25 to 75 %) were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
2
8
0
3
Order By: Relevance
“…The shorter time to reach maximum muscle relaxation (TOF 0 ) for women, and the longer time to reach TOF 25 indicating the beginning of the reduction of the neuromuscular block effect and to reach TOF 90 indicating the return of muscle power supports this idea [15,17].…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The shorter time to reach maximum muscle relaxation (TOF 0 ) for women, and the longer time to reach TOF 25 indicating the beginning of the reduction of the neuromuscular block effect and to reach TOF 90 indicating the return of muscle power supports this idea [15,17].…”
Section: Discussionsupporting
confidence: 48%
“…In a study of 848 patients using total intravenous anesthesia (TIVA), Adamus et al [17] compared the TOF 0 , TOF 25 and TOF duration after induction with 0.6 mg kg-1 rocuronium. At the end of the study it was observed that the time to reach TOF 0 (91.7±14.3 s compared to 108.0±14.6 s) was shorter for women than for men, while the times to reach TOF 25 (43.3±7.8 min compared to 31.3±5.5 min) and TOF (15.2±5.1min compared to 14.7±4.0 min) were longer.…”
Section: Discussionmentioning
confidence: 99%
“…We designed a study to compare the i-gel TM with the AuraOnce TM under conditions of controlled ventilation. Due to the fact that some of the procedures required muscle relaxation 7,8 , and to provide homogenous conditions for device insertion, we decided to administer a nondepolarizing muscle blocker to all patients. The primary outcome measure was seal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…This result seems to be caused by the higher number of female patients in this study [17,18]. There are differences in terms of the pharmacodynamics of the drug used for anesthesia depending on gender and it has been reported that females were 20-30% more sensitive to muscle relaxant than males [17,18]. …”
Section: Discussionmentioning
confidence: 86%